The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1590/s1517-707620150001.0017
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of coconut fiber surface under chemical treatment

Abstract: The objective of this study was to determine the effect of chemical treatment on the coconut fiber surface morphology. This study is divided into three stages, preparation of materials, treatment and testing of coconut fiber. The first treatment is coconut fiber soaked in a solution of NaOH for 3 hours with concentration, respectively 5%, 10%, 15%, and 20%. The second treatment is coconut fiber soaked in KMnO 4 solution with a concentration of 0.25%, 0.5%, 0.75%, and 1% for 3 hours. The third treatment is coco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 12 publications
4
21
1
4
Order By: Relevance
“…The SEM analysis is suitably utilized also to relate with the textural aspects of the sensorial properties of coconut grating. The change in surface morphology of coconut fiber with chemical treatment has been reported by Arsyad, Wardana, and Irawan (), where the coconut fiber was observed to become rough with a decrease in mechanical strength. The surface morphology of coconut fiber with and without chemical treatment has been reported by Arsyad et al () and chemical treatment has changed the surface morphology of coconut fiber and became rough with a decrease in mechanical strength.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…The SEM analysis is suitably utilized also to relate with the textural aspects of the sensorial properties of coconut grating. The change in surface morphology of coconut fiber with chemical treatment has been reported by Arsyad, Wardana, and Irawan (), where the coconut fiber was observed to become rough with a decrease in mechanical strength. The surface morphology of coconut fiber with and without chemical treatment has been reported by Arsyad et al () and chemical treatment has changed the surface morphology of coconut fiber and became rough with a decrease in mechanical strength.…”
Section: Resultssupporting
confidence: 63%
“…The change in surface morphology of coconut fiber with chemical treatment has been reported by Arsyad, Wardana, and Irawan (), where the coconut fiber was observed to become rough with a decrease in mechanical strength. The surface morphology of coconut fiber with and without chemical treatment has been reported by Arsyad et al () and chemical treatment has changed the surface morphology of coconut fiber and became rough with a decrease in mechanical strength. Raghavendra et al () reported rupture in honey comb fiber matrix structure of coconut grating which was subjected to different mechanical operations.…”
Section: Resultssupporting
confidence: 63%
“…Generally to know the roughness of fiber surface always use SEM [1,2,3,4]. Therefore, in this study also used the measurement directly by using the surface roughness gauge Mitutoyo SJ.301 [4,8].…”
Section: Measured Of Surface Roughness By Mitutoyo Sj301mentioning
confidence: 99%
“…Lignin is a macromolecular polyphenol compound whereas cellulose and hemicellulose are polysaccharide compounds. Natural fibers are also hydrophilic, meaning they are easy to absorb water [1] [2]. This will result in low of bonding strength between natural fibers and matrix, in addition to fiber surfaces still containing impurities and other elements [3].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, natural fibers have been widely studied by experts as industrial materials such as mengkuang fibers, palm fibers, akaa (corypha) fibers, king pineapple leaf fibers, coconut fibers, carica papaya fibers, albizia amara fibers, and juncus effuses L fibers [1][2][3][4][5][6][7][8][9]. This study discusses the treatment of Sago fiber (SF) using acetic acid in liquid smoke from coconut shell which is more eco-friendly than other alkali treatment.…”
Section: Introductionmentioning
confidence: 99%